In the making : identity formation in South Asia - Meeto -2006. (New Delhi : Three Essays Collective, 2007)
Articles with reference to South Asia.
Includes bibliographical references.
Keywords: Group identity -- South Asia -- Historiography; South Asia -- Ethnic relations -- Historiography; South Asia -- Civilization -- 19th century